Improving Operational Efficiency In Image-Guided Biopsy Clinics: A Lean Six Sigma Approach Integrating Radiology, Nursing, Pharmacy, And Health Services Administration (The Review of Diabetic Studies, 2025)
Background:Image-guided biopsy clinics play a critical role in modern diagnostic pathways by enabling accurate tissue sampling with minimal invasiveness. Despite advances in imaging technologies, many biopsy services continue to face operational inefficiencies, including prolonged patient wait times, workflow interruptions, suboptimal resource utilization, and coordination challenges among multidisciplinary teams. These inefficiencies may negatively affect patient safety, satisfaction, diagnostic turnaround time, and overall healthcare value.Problem statement:Operational inefficiencies in image-guided biopsy clinics often arise from fragmented workflows, inadequate interprofessional coordination, and limited application of structured quality improvement methodologies across radiology, nursing, pharmacy, and health services administration. Addressing these challenges requires a comprehensive systems-based approach that integrates clinical and administrative perspectives.Aim:This paper aims to critically examine the role of Lean Six Sigma methodologies in improving operational efficiency in image-guided biopsy clinics through multidisciplinary integration of radiology, nursing, pharmacy, and health services administration.Methods:An original narrative literature review was conducted, drawing on peer-reviewed publications addressing Lean Six Sigma applications in healthcare, diagnostic imaging, nursing workflow optimization, pharmacy operations, and health services management. The Lean Six Sigma framework, particularly the Define–Measure–Analyze–Improve–Control (DMAIC) cycle, was used as an analytical lens to synthesize evidence related to process optimization, waste reduction, and performance improvement in biopsy clinic settings.Results:The reviewed literature demonstrates that Lean Six Sigma implementation is associated with measurable improvements in patient flow, reduced procedure turnaround time, enhanced staff coordination, decreased medication-related delays, and improved utilization of imaging resources. Multidisciplinary engagement consistently identified as a critical success factor, with radiology-led workflow redesign, nursing-driven patient preparation optimization, pharmacy-supported medication management, and administrative governance contributing synergistically to operational gains.Conclusion:Lean Six Sigma offers a robust, evidence-informed framework for enhancing operational efficiency in image-guided biopsy clinics. Integrating radiology, nursing, pharmacy, and health services administration within a unified quality improvement strategy can lead to sustainable improvements in clinical performance, patient experience, and organizational value.